Factor analysis of life skills constructs in geographical learning - Mulyadi Yudia (E3S Web of Conferences)
This study aims to identify key predictors of life skills in geography learning, essential for students’ independent quality of life in the 21st century. Using a quantitative descriptive method, 351 Grade XII social science students from SMAN 3, 6, 7, 8, and 10 Tasikmalaya were selected via random sampling. Data collection involved questionnaires based on geography learning characteristics, life skills, and relevant regulations. Analysis with SPSS 24 for Bivariate Pearson correlation revealed significant relationships between variables, such as Geographic Knowledge with Geographic Information Identification (r=0.726), Problem Solving (r=0.741), and Decision Making (r=0.735). Further, factor analysis using AMOS 22 confirmed model fit across three Goodness-of-Fit measures: Absolute Fit (χ²=5.649, p=0.059, CMIN/DF=2.825, GFI=0.992, RMSEA=0.072), Incremental Fit (AGFI=0.959, TLI=0.989, NFI=0.994), and Parsimonious Fit (PNFI=0.331, PGFI=0.198). Findings indicate that geography knowledge is a strong predictor of essential life skills like decision-making and problem-solving. This research underscores the value of applied geography knowledge to foster students’ life skills, equipping them to utilize knowledge as opportunities in modern society.